2005
DOI: 10.1002/hep.20842
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Pediatric Nonalcoholic Fatty Liver Disease * #

Abstract: Nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) are common in children and adolescents. However, standard histological criteria for pediatric NAFLD and NASH are undeveloped. We reviewed consecutive patients ages 2 to 18 years with biopsy-proven NAFLD diagnosed between 1997 and 2003. Biopsies were evaluated by two pathologists for individual features of steatohepatitis. Agglomerative hierarchical cluster analysis demonstrated two different forms of steatohepatitis. Type 1 was ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
648
5
19

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 679 publications
(699 citation statements)
references
References 45 publications
27
648
5
19
Order By: Relevance
“…Diagnosis of NASH was formulated in 38 patients (NASX5), a diagnosis of simple steatosis (NASp2) was made in 41 patients; whereas 41 were considered indeterminate. When the criteria of Schwimmer et al 27 were applied, only 3% patients met the criteria for NASH type 2 diagnosis, and 30% children encountered the criteria for NASH type 2. Most patients showed an overlapping of NASH types 1 and 2 (54%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of NASH was formulated in 38 patients (NASX5), a diagnosis of simple steatosis (NASp2) was made in 41 patients; whereas 41 were considered indeterminate. When the criteria of Schwimmer et al 27 were applied, only 3% patients met the criteria for NASH type 2 diagnosis, and 30% children encountered the criteria for NASH type 2. Most patients showed an overlapping of NASH types 1 and 2 (54%).…”
Section: Resultsmentioning
confidence: 99%
“…16,27 The syndrome occurs in 4.2% of healthy adolescents. 28 Its prevalence increases to 6.1 and 28.7% in overweight and obese adolescents, respectively, 27 and, according to this report, it achieves the rate of 66% in children with fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated NAFLD prevalence was 9.6% when adjusted for age, gender, race and ethnicity. 184 Multivariate analyses showed that obesity, older age (in adolescence), male gender, and Hispanic ethnicity are independent predictors of fatty liver prevalence.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Children are reported with NAFLD as early as 2 years and with NASH-related cirrhosis as early as age 8. 183,184 Prevalence and Risk Factors…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…3 One hundred consecutive liver biopsies from children ages 2 to 18 years were reviewed. Ninety-eight percent of the children were either obese or overweight and 8% were diabetic.…”
mentioning
confidence: 99%